Victimological review of peer violence in the digital environment - Mirić Filip; Vasiljević-Prodanović Danica (Temida)
Using information and communication technologies is one of the basic competencies of modern people. The Internet has enabled the download and sharing of data in digital form, learning, information, business, entertainment, and inclusion in social networks. However, the development of the Internet has also led to the emergence of various forms of digital violence. Minors who cannot adequately react to this violence are particularly susceptible to victimisation. The subject of this paper is the phenomenon of peer violence in the digital environment, viewed from a victimology perspective. The paper presents the basic phenomenological characteristics of this form of violence and the typology of victims and perpetrators. This paper aims to point out the importance of a victimology approach to the problem of cyber violence and the need to implement programs to prevent violence and protect victims of peer violence in the digital environment. By comparing the characteristics of perpetrators and victims in the digital environment, we can gain valuable insights that can contribute to the prevention of this form of peer violence.